1993
DOI: 10.1891/0047-2220.24.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Successful Vocational Rehabilitation of Substance Abusers

Abstract: This study compared vocational rehabilitation clients with substance abuse disabilities to clients with other disabilities, and it compared successfully and unsuccessfully rehabilitated substance abuse clients in order to identify factors which might further promote successful outcomes. Comparisons suggest that substance abusers may have greater obstacles to employment, such as more criminal involvement. Substance abusers received slightly more services, were nearly as likely to be successfully rehabilitated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
1
5
1
1
Order By: Relevance
“…Our replication and extension of the findings of Schwab and DiNitto (1993) as well as McAweeney et al (2008) suggest that persons with SUD who successfully complete VR, both with an official diagnosis as demonstrated in the earlier research, or based on a positive screening result as Note. Reasons for closure codes are 0: achieved employment outcome, 6: transferred to another agency; 1: unable to locate or contact, 3: refused services or further services, 5: individual in institution, 7: failure to cooperate.…”
Section: Summary Of Findingssupporting
confidence: 73%
See 2 more Smart Citations
“…Our replication and extension of the findings of Schwab and DiNitto (1993) as well as McAweeney et al (2008) suggest that persons with SUD who successfully complete VR, both with an official diagnosis as demonstrated in the earlier research, or based on a positive screening result as Note. Reasons for closure codes are 0: achieved employment outcome, 6: transferred to another agency; 1: unable to locate or contact, 3: refused services or further services, 5: individual in institution, 7: failure to cooperate.…”
Section: Summary Of Findingssupporting
confidence: 73%
“…Contrary to Schwab and DiNitto (1993), McAweeney et al (2008) found the cost of providing services to individuals with SUD to be slightly higher than cost of services to consumers without an SUD diagnosis, perhaps due to the greater number of services received by the consumers in the later study. The common predictors in these two studies were the identification of SUD early in the process and participating in VR for a shorter amount of time.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…As agencies and counselors have traditionally been evaluated by number of successful closures, researchers have also frequently evaluated outcomes for state-federal VR consumers related to whether they achieved employment (e.g., Butterworth, Schalock, & Gilmore, 1998;Caston & Watson, 1990;Hill, 1989;Moore, Flowers, & Taylor, 2000;Schwab & DiNitto, 1993). Other authors have attempted to evaluate VR consumer outcomes beyond obtainment of employment at closure.…”
mentioning
confidence: 99%
“…Little, if any, research has focused on interventions or strategies for counseling individuals with disabilities and substance use disorders. It is estimated that up to 33% of consumers of vocational rehabilitation services have substance use disorders (Schwab & DiNitto, 1993) and 22% report being in recovery (Glenn, Ford, Moore, & Hollar, 2003). With the prevalence rate of substance use disorders among persons with disability higher than that for the general population (Moore & Li, 1994), it seems prudent for the field to begin exploring rehabilitation counseling issues related to this group.…”
Section: A Convergence Of Research On Adaptation and Recovery The Impmentioning
confidence: 99%